Analisa Kelayakan Finansial Pengembangan Cold Storage Plant di Pelabuhan Perikanan Lampulo Baru Banda Aceh - Juanda Juanda; Martunis Martunis (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
The research aims to analyze financial feasibility of cold storage development in Lampulo Baru Fish Port Banda Aceh in accordance with discounted investment ctiteria; Net Present Value (NPV), Net Benefit Cost Ratio (NBCR), Gross Benefit Cost Ratio (GBCR) and payback period (PBP). The research was conducted in Lampulo Baru Fish Port on November 2013 – January 2014. Data was mainly collected by using survei and interview/ focus group discussion techniques. Data were analyzed by using financial analysis with investment criteria. The result of research showed that the development of cold storage plant in Lampulo Baru Fish Port with capacity of 80 ton fishes is financially feasible, indicated by discounted investment criteria values; NPV = IDR. 1,463,819,997,-. NBCR = 2.33, GBCR = 1.03,  and PBP = 2.33 years.